PENGARUH BOARD GENDER DIVERSITY & GCG TERHADAP FIRM PERFORMANCE PADA PERUSAHAAN SEKTOR BARANG KONSUMSI YANG TERDAFTAR DI BEI PERIODE 2012 - 2016 - Lisa Marcelina Felinda; Putu Anom Mahadwartha; Endang Ernawati (Perpustakaan Universitas Surabaya, 2018)
This study aims to analyze the effect of board gender diversity, board size, blockholder ownership, firm size, and leverage towards financial firmperformance using Tobin’s Q as a proxy in consumer good sector companies listed in Indonesia Stock Exchange (BEI) in the period 2012-2016. This research uses quantitative approach with multiple regression analysis model. This study uses sample of firms which are listed on consumer good sector in IDX on 2012 -2016. The number of final samples used in this study were 34 business entities with 170 observations. This study uses DWOMEN and PWOMEN to measure board gender diversity. The findings result of this research DWOMEN, PWOMEN, B_SIZE, BHR_OWN and F_SIZE have positive and significant effect towards Tobin’s Q in consumer good sector companies BEI on the period 2012-2016, while LEV have negatif but insignificant effect towards Tobin’s Q in consumer good sector companies BEI on the period 2012-2016.